The effect of preparatory therapy with myo-inositol on the outcome of infertility treatment by ART in men with low reproductive function - O.M. Feskov; Y.S. Zhylkova; H.V. Nesteruk; I.K. Osovskyi; А.О. Feskova (Publishing House TRILIST, 2021)
Research objective: to study the effect of myo-inositol (MI), folic acid (FA) and cyanocobalamin in mono- and complex therapy on the classical fertility rates and the level of DNA fragmentation in sperm in men with low reproductive function, and on the results of the in vitro fertilization (IVF) programs performed in these patients. Materials and methods. A retrospective study of 133 patients aged 32 to 40 years was carried out for the period 2020-2021. All patients were divided into three groups: group 1 - 44 men who took MI, FA and cyanocobalamin daily as monotherapy for 3 months; group 2 - 42 patients who followed a diet to improve spermatogenesis for 3 months; group 3 - 47 men, for whom complex therapy was applied for 3 months: MI, FA, cyanocobalamin and diet. Results. The increase of sperm concentration in ejaculate, improvement of progressively motility of spermatozoa, and increase of the percent of spermatozoa with normal morphology in men with failures of reproductive function after the complex preparatory therapy are defined. The preparatory therapy for men with MI in preparation for IVF helps to improve the quality of embryos and increase the pregnancy rates in couples with male infertility due to the assisted reproductive technologies. The positive effect of preparatory complex therapy in patients with poor spermatogenesis on the blastocyst formation rates in IVF programs is shown. Conclusions. The positive effect of MI on the normal functioning of the reproductive system in men has been proven. The increase pregnancy rates in the IVF program after preparatory treatment of men with MI can be explained by its positive effect on reducing the level of DNA fragmentation of sperm.